UPAYA INDONESIA MENINGKATKAN DAYA SAING PARIWISATA DALAM RANGKA ASEAN TOURISM STRATEGIC PLAN (ATSP) TAHUN 2016-2020 - Azzahra Alwi (2023)
Tourism as one of the fastest growing industries is essential for the Southeast Asian region. ASEAN formed the ASEAN Tourism Strategic Plan (ATSP) with strategic directions to improve the region's tourism competitiveness. The purpose of this study is to determine Indonesia's efforts to improve tourism competitiveness in the framework of the ATSP in 2016-2020. This research uses the concepts of regionalism, tourism, and tourism competitiveness. The method used in the research is qualitative and descriptive research type. Primary data used in this research are documents regarding the ASEAN Tourism Strategic Plan (ATSP) program and Indonesian tourism from the Ministry of Tourism, as well as secondary data obtained from official websites. The results of this study found that Indonesia's efforts to improve tourism competitiveness in the context of the ATSP in 2016-2020 have been successful in improving its tourism competitiveness ranking according to the WEF measurement index. The implementation of the ATSP in Indonesia's tourism policy has helped increase the number of tourists, foreign exchange earnings, and tourism competitiveness rankings.